MODIFIKASI SISTEM OTOMASI PADA SLIDING HOOD GUNA MENINGKATKAN EFISIENSI KERJA DAN MEMPERBAIKI NILAI ERGONOMI BAGI OPERATOR CNC CUTTING DI PT XYZ - Kristiawan, Timotius Anggit; Sugiono, Friska Ayu Fitrianti; Amin, Faiz Sholihul; Bistolen, Boy (Politeknik Negeri Semarang, 2025)
The CNC cutting process at PT XYZ produces emissions and heat controlled by a sliding hood. However, its manual operation—requiring operators to push a 69.65 kg device up to 30 times daily—creates fatigue, discomfort, and low tool utilization. This highlights a gap where automation is often applied for efficiency but rarely combined with ergonomic improvements. This study aims to develop and test an automated sliding hood to increase efficiency and reduce ergonomic risks. The Shigley-Mitchell design methodology was applied, supported by observation, interviews, and performance testing before and after modification. Key indicators measured were cycle time, tool effectiveness, and ergonomic risk using the RULA method. Results showed a decrease in cycle time from 57.28 to 46.65 seconds (18.6% efficiency gain). Tool effectiveness rose from 27 to 44 successful operations out of 45, while RULA scores improved from 7 (high risk) to 3 (low risk), indicating a 58% ergonomic improvement. In conclusion, automating the sliding hood enhanced work efficiency, optimized equipment use, and improved ergonomic conditions. This demonstrates the value of integrating automation with ergonomic design to achieve productivity and health benefits in manufacturing.